Biomedical Informatics and Granularity. Issue 6 (2004) - Kumar, Anand; Smith, Barry; Novotny, Daniel D.
Abstract : An explicit formal-ontological representation of entities existing at multiple levels of granularity is an urgent requirement for biomedical information processing. We discuss some fundamental principles which can form a basis for such a representation. We also comment on some of the implicit treatments of granularity in currently available ontologies and terminologies (GO, FMA, SNOMED CT).